How Clonal Is Clonal? Genome Plasticity across Multicellular Segments of a “Candidatus Marithrix sp.” Filament from Sulfidic, Briny Seafloor Sediments in the Gulf of Mexico - Salman-Carvalho, Verena; Fadeev, Eduard; Joye, Samantha B.; Teske, Andreas (Frontiers in Microbiology, 2016)
"Candidatus Marithrix" is a recently described lineage within the group of large sulfur bacteria (Beggiatoaceae, Gammaproteobacteria). This group of bacteria comprises vacuolated, attached-living filaments that inhabit the sediment surface around vent and seep sites in the marine environment. A single filament is ca. 100 µm in diameter, several millimeters long, and consists of hundreds of clonal cells, which are considered highly polyploid. Based on these characteristics, "Candidatus Marithrix" was used as a model organism for the assessment of genomic plasticity along segments of a single filament using next generation sequencing to possibly identify hotspots of microevolution. Using six consecutive segments of a single filament sampled from a mud volcano in the Gulf of Mexico, we recovered ca. 90% of the "Candidatus Marithrix" genome in each segment. There was a high level of genome conservation along the filament with average nucleotide identities between 99.98-100%. Different approaches to assemble all reads into a complete consensus genome could not fill the gaps. Each of the six segment datasets encoded merely a few hundred unique nucleotides and 5 or less unique genes - the residual content was redundant in all datasets. Besides the overall high genomic identity, we identified a similar number of single nucleotide polymorphisms (SNPs) between the clonal segments, which are comparable to numbers reported for other clonal organisms. An increase of SNPs with greater distance of filament segments was not observed. The polyploidy of the cells was apparent when analyzing the heterogeneity of reads within a segment. Here, a strong increase in single nucleotide variants, or 'intrasegmental sequence heterogeneity' (ISH) events, was observed. These sites may represent hotspots for genome plasticity, and possibly microevolution, since two thirds of these variants were not co-localized across the genome copies of the multicellular filament.